Disfunções metabólicas na adolescência : um fator de risco para o desenvolvimento de doenças cardiovasculares - Souza, Joice Lilian Porfirio de (2023)
Systemic arterial hypertension (SAH) is a public health problem given its high prevalence, low control rate and extensive risk factors. Among other, SAH has been associated with sociodemographic, behavioral and clinical factors, as well as to the paradigm of developmental origins of health and disease (DOHaD), in which its origin is associated with exposure to neuroendocrine insults in critical stages of live development. Our aim was to assess the metabolic profile of adolescents in both of sexes and its correlation with cardiovascular risk. A cross-sectional study was carried out, in which 217 adolescent students from public schools in the city of Sinop, MT, Brazil were evaluated. A semi-structured interview was carried out with previously formulated questions, referring to sociodemographic, behavioral and eating habits that were addressed to the adolescents and their parents. The participants in the study were classified according to their body mass index (BMI) as eutrophic (Eut group) and overweight (Sob group). The lipid profile, insulinemia, glycemia were assessed and anthropometric parameters taken for analysis of the BMI and adiposity index, through the waist-hip ratio (WHR). Systolic (SBP) and diastolic (DBP) blood pressure and heart rate (HR) were measured. Data were submitted to a normality test and subsequently analyzed by appropriate statistical tests. Our study detected that 69.5% of the adolescents are Eut and 30.4% Sob (P<0.05). Compared to the Eut group, the Sob, of both genders, showed more prominent alterations, with increased mean values (P<0.05), where 7.1% increase in WHR, 7.0% increase in total cholesterol, and 11.8% in LDL-cholesterol. In addition, we observed that Sob individuals showed an increase of 4.3% in SBP and 7.1% in DBP, as well as a 36.1% increase in the Castelli II index. Compared to Eut boys, Sob adolescents displayed increased values of TyG (2.3%, P<0.05), glycemia (4.0%, P<0.05), VLDL-cholesterol (33.0%, P<0.05) and reduction in HDLcholesterol (11.3%, P<0.05), which was not observed in but not Sob girls. In conclusion, overweight adolescents, analyzed herein, presented increased in many metabolic syndrome markers (SBP, dyslipidemia, insulin resistance), as well as greater risk for the development of atherosclerosis in both sexes, although boys are at greater risk than girls. In addition, we conclude that the occurrence of SAH in overweight adolescents was not associated with birthweight or alterations in cardiac function.